Characterization of protein redox dynamics induced during light-to-dark transitions and nutrient limitation in cyanobacteria - Ansong, Charles; Sadler, Natalie C.; Hill, Eric A.; Lewis, Michael P.; Zink, Erika M.; Smith, Richard D.; Beliaev, Alexander S.; Konopka, Allan E.; Wright, Aaron T. (Frontiers in Microbiology, 2014)
Protein redox chemistry constitutes a major void in knowledge pertaining to photoautotrophic system regulation and signaling processes. We have employed a chemical biology approach to analyze redox sensitive proteins in live Synechococcus sp. PCC 7002 cells in both light and dark periods, and to understand how cellular redox balance is disrupted during nutrient perturbation. The present work identified 300 putative redox-sensitive proteins that are involved in the generation of reductant, macromolecule synthesis, and carbon flux through central metabolic pathways, and may be involved in cell signaling and response mechanisms. Furthermore, our research suggests that dynamic redox changes in response to specific nutrient limitations, including carbon and nitrogen limitations, contribute to the regulatory changes driven by a shift from light to dark. Taken together, these results contribute to a high-level understanding of post-translational mechanisms regulating flux distributions and suggest potential metabolic engineering targets for redirecting carbon towards biofuel precursors.